The Role of Host Plants, Alternative Food Resources and Herbivore Induced Volatiles in Choice Behavior of an Omnivorous Predator - Maselou, Dionyssia A.; Anastasaki, Eirini; Milonas, Panagiotis G. (Frontiers in Ecology and Evolution, 2019)
Macrolophus pygmaeus, Rambur (Heteroptera, Miridae) is a generalist predator found on various plant species and has also the ability to feed both on animal and plant tissue. Foraging behavior of M. pygmaeus and ultimately its efficacy as a biological control agent, is known to be affected by olfactory stimuli. Here, we elaborate on the response of this omnivore predator to volatiles produced by host plants by conducting olfactometric bioassays under laboratory conditions. In particular, we explored: i) the relationship between previous experience and plant choice of M. pygmaeus nymphs by comparing its attractiveness to pepper and aubergine plants and ii) how the presence of an aphid prey, Myzus persicae (Sulzer), or floral resources may influence choices made by M. pygmaeus. When the two host plants were provided, aubergine plants were found to be more attractive than pepper plants, regardless the previous experience of M. pygmaeus. Furthermore, the presence of M. persicae made aubergine plants more attractive to M. pygmaeus nymphs than uninfested aubergine plants. The gas chromatography-mass spectrometry analysis showed that plants infested with M. persicae emitted additional compounds as compared to the volatiles emitted from uninfested plants. In particular, four compounds, (E)-β-farnesene, (Ε,Ε)-ΤΜΤΤ, 2-methylbutanal oxime and dodecanal were found present only in the headspace of aubergine plants with aphids. However, M. pygmaeus did not show preference for the floral resources. Our results indicate that the response of M. pygmaeus is tuned towards the various stimuli in its habitat.